Evaluation of anemia in non-enhanced and contrast-enhanced dual-energy CT using electron density imaging - Cherry Kim; Suk Keu Yeom; Hangseok Choi; Euddeum Shim; Sung Ho Hwang; Hwan Seok Yong; Marly van Assen; Carlo N. De Cecco; Hwa Jung Sung; Se Ryeon Lee (PLoS ONE, 2026)
Electron density (ED) imaging derived from dual-energy CT (DECT) quantifies tissue composition and may reflect changes in red blood cell (RBC) mass associated with anemia. This study aimed to evaluate the utility of ED from DECT in assessing anemia severity using both non-enhanced CT (NECT) and contrast-enhanced CT (CECT), and to investigate its correlation with hemoglobin (Hb), hematocrit (Hct), and RBC count. In this retrospective study, 2,558 patients who underwent NECT and 2,545 who underwent CECT using a dual-layer spectral detector CT (Philips IQon) were included. Mean ED and mean CT attenuation (HU) were measured at five cardiac blood pool sites. Spearman’s rank correlation analysis was performed between CT measurements and hematologic parameters. Partial correlation analysis adjusting for age and sex and non-parametric bootstrap internal validation were also conducted. Receiver operating characteristic (ROC) curve analysis was performed to determine diagnostic cutoff values for anemia detection. Mean ED significantly decreased with increasing anemia severity in both NECT and CECT cohorts (all p < 0.001). With NECT, mean ED showed positive correlations with Hb, Hct, and RBC count (r s = 0.726–0.770), with AUCs of 0.825–0.956 for anemia detection. With CECT, mean ED retained positive correlations with hematologic parameters (r s = 0.447–0.583), with AUCs of 0.727–0.895, while mean HU showed no meaningful correlation. After adjustment for age and sex, partial correlation coefficients remained substantial (NECT: r s = 0.694; CECT: r s = 0.509 for Hb), and bootstrap internal validation confirmed negligible overfitting bias. ED derived from DECT demonstrated diagnostic utility for anemia detection on NECT, unlike conventional HU, retained clinically relevant associations with hematologic parameters on CECT. ED-based anemia detection on CECT is best conceptualized as opportunistic detection, particularly for severe anemia, supplementary to laboratory testing. These findings require external validation across diverse DECT platforms before broader clinical implementation.